Evaluating State-of-the-Art Computerized Pupillary Assessments for Glaucoma Detection: A Systematic Review and Meta-Analysis - Suo, Lingge; Zhang, Di; Qin, Xuejiao; Li, Annan; Zhang, Chun; Wang, Yunhong (Frontiers in Neurology, 2020)
Computerized pupillary light reflex assessment devices (CPLRAD) may serve as an effective screening tool for glaucomatous optic neuropathy, since it can dynamically detect abnormal PLR from a novel sequence of light stimuli and functionally-shaped stimuli. The aim of this study was systematically evaluate the current state of advanced CPLRAD and accuracy of application in detecting glaucoma. An electronic literature search was performed of PubMed, MEDLINE, and Embase from database inception to December 2019. Studies that reported data on the use of computer-aid pupillometry with monocular and/or binocular monitoring in glaucoma patients were included. Two review authors independently conducted the study selection and extracted study data. A total of 25 studies were included in this review; Eight studies with a total of 829 subjects were included in this meta-analysis. Data were pooled using a random-effects model, since the significant heterogeneity (P<0.1, I2>50%). Our meta-analysis of eight studies showed reasonably high summary sensitivity and specificity estimates of 0.81(95% CI 0.73-0.89) and 0.83(95% CI: 0.75-0.91), respectively. Simpler monochromatic devices, such as, Pupilmetrix™ PLR60, generally performed as well as or slightly better than more complex chromatic devices. This review suggests that CPLRAD may provide direct clinical decision making for glaucoma diagnosis and evaluation, and may provide a deeper understanding of pathomechansim of glaucoma.